(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Although the author states that “there are not quite clear criteria, in accordance with which some words, before they become components, are acknowledged as symbols, and others are not”, but an original symbolic meaning of the component is at least partially kept in semantics of the fixed phrase and quite regularly reproduced in many phraseological units. Moreover, even if a symbolically meaning word is updated in the language, it can vary its semantics to a rather broad extent (Zhukov,1996). A.V. Kunin also believes that it is necessary to take an integrated approach to this issue, which provides a possibility to determine a system of regular differences and common features. In his opinion, the semantic structure of the fixed phrase and the semantic structure of the word are by no means exhausted by their meanings only. Important elements of the semantic structure, in addition to the meaning, are structures of a total formation in general, its grammatical appearance and system language bonds (Kunin, 2005).